Awareness and purchase intention towards edible bird's nest products - Ramalingam, Leelanayagi (2014)
Edible bird‟s nest (swiftlet bird‟s nest) is one of the high value agricultural products which contributes about one percent to the gross domestic product. Being aware of the large role it plays in the economic growth of the country, the Malaysian government has started to give priority to the development of edible bird‟s nest industry in the Tenth Malaysia Plan, Economic Transformation Programme as well as The National Agro-Food Policy. The government‟s support has encouraged the private companies to develop the industry and make Malaysia become the world second largest producer of edible bird‟s nest. However, at this point of time, Malaysia is facing a problem in exporting its edible bird‟s nests to China due to the high levels of nitrate contain. This has caused a big loss for Malaysian edible bird‟s nest industry. The industry has been plagued by over production and this has led to a decline in the market price of edible bird‟s nest. To overcome the decline, the Malaysian government has decided to promote the edible bird‟s nest based products among the locals. Hence, there is a vital need for consumer orientated approach to understanding the market for edible bird‟s nest products in Malaysia. Consequently, the objective of the study is to investigate the awareness and purchase intention of edible bird‟s nest products among Malaysian consumers. Data from 1361 respondents is used to achieve the objective of the study. The questionnaire of the survey includes seven sections which are socio demographic information, awareness and knowledge, perceived value, attitude, subjective norm, perceived behavioural control and intention. The results of the study show that, respondents reveal positive attitudes and intentions towards purchasing edible bird‟s nest products. Structural equation modeling analysis indicates that there is a significant relationship between knowledge, perceived value and attitude. In addition, knowledge, perceived value, attitude, subjective norm and perceived behavioural control also positively and significantly influence consumer purchase intention towards edible bird‟s nest products. Test of mediation effect of attitude and moderation effect of awareness and socio demographic characteristics were positive. Implications for producers, marketers and policy makers are discussed and future research directions are recommended based on the research findings.